PSYCHOANALYTIC ANALYSIS OF THE CONCEPT OF THE HEART IN THE PHILOSOPHY OF ALFRED ADLER (Scientific journal of the Fergana State University, 2024)
In the views of Alfred Adler, the concept of the soul, love, benevolence, friendship, benevolence, proportionality, human serenity, ethics, and the study of human creative possibilities as a result of the emergence of relationships is outlined.  At the same time, the psychoanalytic aspects of human spiritual elevation in Adler's views were analyzed.